Impact of shorter picking intervals on the storability and postharvest quality of rabbiteye blueberries cv. ‘Brightwell’ - Godara, Amit; Rubio Ames, Zilfina; Deltsidis, Angelos (Frontiers in Plant Science, 2025)
The quality and shelf-life of fresh-market blueberries are crucial aspects for both growers and consumers. Different picking intervals could be affecting these factors, and understanding changes associated with these issues is essential to optimize postharvest fruit performance. This study evaluated the impacts of different picking intervals on the postharvest quality and storability of rabbiteye blueberries (Vaccinium virgatum) cv. ‘Brightwell’ in Georgia, USA, during the 2023 and 2024 seasons. Harvesting was carried out at intervals of two days (Trt A), three days (Trt B), and seven days (Trt C), with three harvests per treatment. The main quality parameters assessed included berry damage (%), berry diameter, weight loss, firmness, total soluble solids, titratable acidity, and total anthocyanin concentration, measured over 21 days of storage at 1 °C and 85% relative humidity. Results demonstrated that fruit harvested with the Trt C (seven days interval) exhibited significantly higher weight loss of up to 15.5% at 21 days after storage in 2024, greater berry damage (ranging from 27% to 41.5%), and lower firmness (151.6-155.0 g·mm−1 at harvest 3) than shorter harvesting intervals treatments. Conversely, the 7-day interval yielded higher total soluble solids at harvest 3 (14.0%) versus 2- and 3-day intervals (12.5-13.2%), lower titratable acidity than the 2-day interval (Trt A highest at 1.51-1.53% at Harvest 3), and the highest total anthocyanins (Trt C: 258.9-267.2 mg·L−1). Frequent harvesting (Trt A and B) helped maintain higher fruit firmness, reduced weight loss, and minimized postharvest berry damage while maintaining optimal sugars and acid levels. These findings highlight the importance of optimizing picking intervals, indicating that a three-day picking interval (Trt B) is an effective option for maintaining postharvest fruit quality and storage potential for fresh market blueberries. The 7-day interval (Trt C) produced fruit with higher anthocyanin content, total soluble solids, and lower firmness, indicating greater suitability for processing rather than fresh market use. This study provides valuable insights for blueberry growers aiming to improve the postharvest life of rabbiteye blueberries under warm and humid climate conditions.